A life cycle assessment method to support cities in their climate change mitigation strategies. (October 2022) - Dorr, Erica; François, Cyrille; Poulhès, Alexis; Wurtz, Aurore
Highlights: An original LCA method that combines the food, mobility and building sectors at the city scale. Consumption footprint assessment at the resident, block and city scales. An ambitious policy and behavior change mix has only a relative impact on a city's carbon footprint. Environmental contributions differ substantially between neighborhoods. Abstract: National climate change mitigation objectives must be translated to the city level and to specific sectors, with locally-relevant policy measures. However, assessing the decarbonization value of these measures is a challenge for local policy makers and few local consumption assessment studies integrate a systemic vision. This research presents a multi-criteria city-scale Life Cycle Assessment method focusing on the three largest carbon-emitting sectors in cities: food, residential buildings and daily mobility, with an original combination of databases and models. For food, databases were used to evaluate environmental impacts based on socio-demographic characteristics. For building and mobility,  modeling tools were used and adapted at different scales: with local spatial refinement for mobility and the creation of archetypes representing the city's most common residential buildings. A demonstration of this new cross-sectoral method was conducted on Montreuil city in the Parisian region, to (1) evaluate the current greenhouse gas emissions (GHG), and (2) test the possible reductions following different measures. The developed assessment framework provides various interpretation, with disaggregated contribution, mapping, and scenario analysis. For instance, the application of ambitious measures and important lifestyle changes reduced GHG in these sectors by 30%, far from the French government's ambitions of a 55% reduction by 2030.